Identifying behaviour change techniques within randomized trials of interventions promoting deceased organ donation registration. Issue 3 (10th December 2021) - Crawshaw, Jacob; Li, Alvin H.; Garg, Amit X.; Chassé, Michaël; Grimshaw, Jeremy M.; Presseau, Justin
Abstract : Objective: Increasing deceased organ donation registration may increase the number of available organs for transplant to help save lives. This study aimed to identify which behaviour change techniques (BCTs; or 'active ingredients') are reported within randomized trials of interventions promoting deceased organ donation registration and of those, which are associated with a larger intervention effect. Methods: We conducted a secondary analysis of 45 trials included in a Cochrane systematic review of deceased organ donation registration interventions. Two researchers used the BCT Taxonomy v1 to independently code intervention content in all trial groups. Outcome data were pooled and we used meta‐regression to explore associations between individual and combinations of recurring BCTs and effect on registration intention and/or registration behaviour. Results: A total of 27 different BCTs (mean = 3.7, range = 1–9) were identified in intervention groups across the 45 trials. The five most common BCTs were: 'Information about health consequences' (71%); 'Instruction on how to perform the behaviour' (47%); 'Salience of consequences' (40%); 'Adding objects to the environment' (28%); and 'Credible source' (27%). Comparator groups in 20/45 trials also included identifiable BCTs ( n  = 12, mean = 3.1, range = 1–7). Meta‐regression revealed that a combination of the three most common BCTs was associated with a larger intervention effect size for registration behaviour ( k  = 8, β = .19, p  = .02). Conclusions: Trials of deceased organ donation registration interventions focus predominantly on providing information, instruction, and a means to register. While potentially effective, a much wider set of possible BCTs could be leveraged to address known barriers to registration.